2009
DOI: 10.17305/bjbms.2009.2862
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Symptomatic Epilepsy in Patients with Brain Tumours

Abstract: The aim of our work is to determine the total number, age, gender of the patients with the symptomatic epileptic seizures associated with brain tumours, tumour location, clinical signs and characteristics of epileptic seizures. We have analyzed medical documentation of the patients with brain tumours hospitalized at the Department of Neurology, University of Sarajevo Clinics Centre. This study is retrospective and includes time period from 1st January 2000 until 31st December 2005. During the observed period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…2. Studies including variable seizure types [9][10][11][12]. The mechanism of each seizure type is distinct, and this may have important implications for SEGP and TASE biology.…”
Section: Introductionmentioning
confidence: 99%
“…2. Studies including variable seizure types [9][10][11][12]. The mechanism of each seizure type is distinct, and this may have important implications for SEGP and TASE biology.…”
Section: Introductionmentioning
confidence: 99%
“…He or she may also fall asleep for varied time periods. Afterwards, the loved one may have muscle soreness, fatigue, or a headache EEG electroencephalogram anoxia, and infectious diseases (Alajbegović et al 2009;Channing Bete Company 2008;Devinsky 2008;Lee and Clason 2008;Mantoan and Kullmann 2011;Martin et al 2006;National Institute of Neurological Disorders and Stroke 2012;Reuber et al 2009; The National Epilepsy Educational Alliance 2009; Wyllie 2010; see Chaps. 4, 6, 7, and 10 correspondingly for a more in-depth discussion of moderate to severe traumatic brain injuries, cerebrovascular accidents, and brain tumors).…”
Section: Family Psychotherapy For Seizure Disordersmentioning
confidence: 99%
“…Patients with more severe hemorrhagic strokes creating cortical damage are at higher risk of developing seizures (Beghi et al 2011;Burneo et al 2010;Szaflarski et al 2008). Based on the literature, the incidence of seizures in brain tumor patients ranges from approximately 20% to as high as 85% (Alajbegović et al 2009;; see Drappatz and Wen 2011, for a review; see Liigant et al 2001, for a review;Mogensen 2008;van Breemen et al 2009;Vercueil 2011). They are more prevalent in patients with low-grade, slow-growing tumors (e.g., astrocytomas, mixed gliomas, and oligodendrogliomas) commonly affecting the frontal and temporal lobes (see Drappatz and Wen 2011, for a review; see Kurzwelly et al 2010, for a review; see Liigant et al 2001, for a review;see Vercueil 2011, for a review).…”
Section: Family Psychotherapy For Seizure Disordersmentioning
confidence: 99%
“…Of these, five had seizures at presentation and seven had delayed seizures. Alajbegovic et al [27] conducted a retrospective study and found that single seizure occurred most often (59%); a series of seizures is relatively uncommon (38%). Status epilepticus occurred in only 3% of patients.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The most common type of seizures were simple partial seizures with or without secondary generalization (66% of seizures were simple partial seizures: 44% of which occurred without generalization and 22% occurred with generalization), followed by generalized convulsive seizures (31%), and finally, the least common type, complex partial seizures (3%) [27]. Ramamurthi et al [28] reported that partial seizures are often associated with lesions in perirolandic areas affecting M1, S1, the supplementary motor area or the secondary somatosensory cortex.…”
Section: Clinical Featuresmentioning
confidence: 99%